2017
DOI: 10.3389/fnhum.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Altered Rich-Club and Frequency-Dependent Subnetwork Organization in Mild Traumatic Brain Injury: A MEG Resting-State Study

Abstract: Functional brain connectivity networks exhibit “small-world” characteristics and some of these networks follow a “rich-club” organization, whereby a few nodes of high connectivity (hubs) tend to connect more densely among themselves than to nodes of lower connectivity. The Current study followed an “attack strategy” to compare the rich-club and small-world network organization models using Magnetoencephalographic (MEG) recordings from mild traumatic brain injury (mTBI) patients and neurologically healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Reduced rich club connectivity in patients with TBI might indicate that it is difficult for these patients to maintain or repair the core network given the biological cost. These results are in conflict with the increased rich club connectivity that was observed in studies examining rich club organization in patients with TBI based on functional MRI data (Antonakakis et al, 2017;Hillary et al, 2014). In contrast to reported converging results in healthy adults when directly comparing functional and structural networks (Honey et al, 2009;Meier et al, 2016;Skudlarski et al, 2008; van Reijmer et al (2015) in older adults with white matter hyperintensities for example demonstrated a clear decoupling.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Reduced rich club connectivity in patients with TBI might indicate that it is difficult for these patients to maintain or repair the core network given the biological cost. These results are in conflict with the increased rich club connectivity that was observed in studies examining rich club organization in patients with TBI based on functional MRI data (Antonakakis et al, 2017;Hillary et al, 2014). In contrast to reported converging results in healthy adults when directly comparing functional and structural networks (Honey et al, 2009;Meier et al, 2016;Skudlarski et al, 2008; van Reijmer et al (2015) in older adults with white matter hyperintensities for example demonstrated a clear decoupling.…”
Section: Discussionmentioning
confidence: 77%
“…To date, only two studies have explored the rich club organization using graph theoretical analysis in adults with TBI (Antonakakis, Dimitriadis, Zervakis, Papanicolaou, & Zouridakis, ; Hillary et al, ), albeit studying functional connectomes (using functional MRI). The results of these studies show increased functional connectivity in the rich club of patients with TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitriadis et al (2015b) using phase-synchronization quantified intra-frequency couplings at the sensor level and showed that significantly different patterns were seen mostly in the delta band, whereas Alhourani et al (2016) used the same metric at the source level and showed reduced local efficiency in different brain regions in mTBI patients. In a follow-up study, Antonakakis and colleagues (2015, 2016, 2017a) showed less dense for mTBIs in which was in line with (Rapp et al, 2015), and later (Antonakakis et al, 2017b) that mTBIs obtained a higher synchronization among rich-club hubs. More recently, Li et al (2018) showed a denser causality network for mTBI patients, whereas Kaltiainen et al (2018) underlined that aberrant theta-band activity can provide an early objective sign of brain abnormality after mTBI.…”
Section: Introductionmentioning
confidence: 70%
“…The current study included fifty right-handed healthy controls (HC) (29.25 ± 9.1 years of age) and thirty right-handed mTBI patients (29.33 ± 9.2 years of age) (Gouridakis et al, 2012). All clinical information including selection criterions and patients’ demographics were reviewed and provided by certified clinicians and they are available in our previous studies (Gouridakis et al, 2012; Antonakakis et al, 2016; 2017a,b). The HC group was determined at UTHSC-Houston and the recruitment of the mTBI patients was done by three trauma centers in the greater Houston metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the aforementioned methodological evidences in microscale, it is significant to explore the repertoire of intra and cross frequency interactions across brain rhythms and brain areas under the same integrated graph model (Antonakakis et al, 2017;Dimitriadis et al, , 2017bDimitriadis et al, , 2018a.…”
Section: Introductionmentioning
confidence: 99%